2021
DOI: 10.1039/d1ra01269j
|View full text |Cite
|
Sign up to set email alerts
|

A highly efficient microwave-assisted synthesis of an LED-curable methacrylated gelatin for bio applications

Abstract: Highly crosslinked gelatin-based hydrogels were prepared via a green technique including a microwave-assisted methacrylation using glycidyl methacrylate or methacrylic anhydride and an LED-curing with a time, energy, and reagent-saving approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 61 publications
(192 reference statements)
0
12
0
Order By: Relevance
“…In Figure S1b, the GelMA spectrum displayed that the peak of CC stretching absorption was concealed by the strong CO stretching peak at 1631 cm –1 . However, C–H bending and CC–H 2 wagging vibrations centered at 556 cm –1 were evidence of successful methacryloyl functionalization of GelMA . Additionally, the absence of a high molecular weight shoulder at shorter retention times in the GPC elution diagrams (Figure S2) suggested that no or minimal premature inter-chain cross-linking or aggregation conducted by the aza-Michael reaction had occurred during the syntheses of CMCSMA and GelMA.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Figure S1b, the GelMA spectrum displayed that the peak of CC stretching absorption was concealed by the strong CO stretching peak at 1631 cm –1 . However, C–H bending and CC–H 2 wagging vibrations centered at 556 cm –1 were evidence of successful methacryloyl functionalization of GelMA . Additionally, the absence of a high molecular weight shoulder at shorter retention times in the GPC elution diagrams (Figure S2) suggested that no or minimal premature inter-chain cross-linking or aggregation conducted by the aza-Michael reaction had occurred during the syntheses of CMCSMA and GelMA.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The methyl peak at 1.83 ppm and acrylate peaks at 5.58 and 5.34 ppm confirmed the methacrylation reaction of gelatin. 53 The lysine methylene peaks at 2.85−2.97 ppm and phenylalanine peaks at 7.10−7.31 ppm of gelatin and GelMA spectra were used to calculate the degree of DM of GelMA according to the previous literature. 54 The result showed that the DM of GelMA was about 52.2%.…”
Section: Syntheses and Characterization Of Cmcsma Andmentioning
confidence: 99%
“…As a result, a relatively large amount of DCPD was observed in ASP conditions at 110 s, 5 c and 110 s, 15 c (Figure S3c,d), while DCPD was not observed in ASP conditions at 10, 5 c and 10 s, 15 c (Figure S3a,b). Therefore, DCPD was generated as a byproduct after ASP for a longer immersion time such as 110 s. Raman spectra (Figure S4) also showed that the deposits contained phosphate because peaks were detected that were derived from the P–O stretching vibration, P–O transformation vibration, and P–O unpaired vibration at 960, 400, 600, and 1000 cm –1 …”
Section: Discussionmentioning
confidence: 99%
“…The amide III peak arises due to the C−N stretching. 55 Shifting of some peaks is observed toward higher wavenumber. These shifts in the peaks confirm strong interactions between the polymer matrix and the nanofillers.…”
Section: Raman Spectroscopy Analysismentioning
confidence: 96%